Exploring patterns of morphological integration in the crania of papio hamadryas ursinus and homo sapiens - Hemingway, Jason (My University, 2017)
Morphological integration is the pattern of correlation or covariation among parts due to genetic, developmental and functional processes, and is essential for the viability of an organism. Integration among processes is not uniform but forms distinct modules allowing for their independent evolvability and is thus central to the study of biological evolution. The incongruence between phylogenies estimated using the genotype and the cranial morphology in both the Papionini primates as well as the Hominidae possibly result from the disregard of character integration. Regarding the degree of morphological integration humans display extremely low levels of integration among the primates, while the baboon possesses extremely high levels. This thesis set out to address three broad aims regarding integration of the baboon and human cranium; namely 1) to study the effect of allometry on measures of integration, and when allometry and sexual dimorphism had been accounted for, 2) to assess the patterning of morphological integration into morphological modules; and finally, 3) to assess differences in the pattern of covariation between the cranial base, cranial vault and facial skeleton in humans and baboons. Although allometric growth is divided into neural and somatic, the findings suggest that the effect of allometry conceals more detailed patterns of morphological integration likely resulting from genetic and developmental processes, and should therefore be accounted for in studies of morphological integration. It is unlikely that allometry among cranial regions constrains evolutionary diversity, but rather offers a path of least resistance. The second aim offered up novel methods of exploring the pattern of morphological covariation using clustering and network methods that supported current hypotheses and proposed that the oral and basicranial regions are comprised of additional modules; however, rigorous scientific scrutiny is required for its support. iv The third aim involved the analysis of integration between the cranial base, cranial vault, and facial skeleton. The results supported the proposal that humans and nonhuman primates share a similar pattern of integration likely reflecting shared developmental processes among the primates, but with key differences probably relating to functional demands. Integration between these three cranial regions primarily involve their relative positioning and proportions. The broad pattern of integration likely reflects the role of the cranium as the supporting framework around the organs and functional capsules, the “real” modules, which accommodate one another epigenetically as they develop. The recognition of both independent modules and their pervasive integration are important and depend primarily on the nature of the investigation.
A thesis submitted in fulfilment of the requirements for the degree of doctor of philosophy to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2017
Keywords: Papio; Bones--Growth